Analysis and Investigation into Microstructure and Mechanical Properties of Dissimilar Welded Joints - Shukaili, Siham Al; R. V., Murali; Fuhaid, Mutlag S. (International Journal For Research In Mechanical & Civil Engineering, 2018)
Welding process is the most commonly used joining process in oil and gas industries especially for manufacturing of heat exchangers, pipelines fabrication etc. Investigation on microstructure and mechanical properties of welded joints is a challenging topic and has more useful benefits. The main aim of this work is to do microstructural analysis of welded joints before and after welding process and relate them with variation in mechanical properties of welded joints. The joints are made up of two different metals to analyse before and after welding process. Stainless steel and carbon steel materials are considered for the investigation as they find more industrial applications such as in steam ship manufacture, high temperature bolts, nuclear reactors etc. because of their excellent resistance to corrosion and high temperature etc. Literature studies reveal that the evaluation of the dissimilar metal weld (DMW) of steels, by different welding processes, was carried out in the past. In this project, tungsten inert gas (TIG) welding process is selected for welding the dissimilar metals and further analysis of the microstructures and mechanical properties. All the welding process is done in our workshop and high-resolution microscope and tensile testing machines (UTM) are used in this project to conduct the mechanical testing and microstructure analysis respectively. Results obtained from these tests are in agreement with the published results. Finally, analysis and interpretation of the results leads to correlating microstructures of the base metals with their mechanical properties such as ultimate tensile strength (UTS), ductility and hardness values.